THE EFFECTIVENESS OF GAMIFICATION TECHNOLOGIES IN ENGLISH LANGUAGE TEACHING - Nazarova Sevinchoy Umarbekovna (TADQIQOTLAR, 2026)
Abstract This article discusses the effectiveness of gamification technologies in English language  teaching.  Increasing  learners’  motivation,  engagement,  and  academic performance is one of the major goals of modern education. This study investigates the use  of  gamification  elements  (points,  badges,  leaderboards,  levels  and  rewards)  to improve  language  learning  outcomes.  The  results  suggest  that  gamification  is beneficial  for  students'  motivation,  participation  and  language  skills.  Additionally, gamified  learning  settings  help  develop  the  abilities  of  independent  learning  and enhance the educational experience through a more interactive approach.